Pengaruh Manajemen Pengetahuan terhadap Kinerja Organisasi Berdasarkan Balance Scorecard pada Lembaga Pemasyarakatan Wilayah Banten - Purba, Asriza; Kusmiyanti, Kusmiyanti (Penerbit Goodwood, 2024)
Purpose: The purpose of this study is to examine the relationship between knowledge management and organizational performance based on balance scorecard method in Banten Correctional Facility Methodology/approach: This study employs a quantitative methodology with focus on data analysis through various statistical tests. Data collected from 188 officials in nine units of Banten Correctional Facility. Results/findings: Knowledge management has a positive and significant effect on organizational performance based on balance scorecard method. Within this context, there are several key factors which enable an organization to stay competitive and innovative such as the application of knowledge creation, knowledge adoption, knowledge adaptation, and knowledge embodiment. Limitations: This research is limited to Banten Correctional Facility, therefore the findings cannot be assumed universally applied to other similar institutions. What’s more, data limitations could affect the analysis subjectively in an effort to provide a better understanding. Contribution: This research has the potential to enrich public understanding by providing valuable insights for all stakeholders involved by highlighting the positive effect of knowledge management and organizational performance being combined through balance scorecard method.